The importance of accounting changes in debt contracts: the cost of flexibility in covenant calculations - Beatty, Anne; Ramesh, K.; Weber, Joseph (Journal of Accounting and Economics, 2002)
In this paper, we examine how the exclusion of voluntary and mandatory accounting changes from the calculation of covenant compliance affects the interest rate charged on the loan. After controlling for self-selection bias and other factors known to affect loan spreads, we find that the rate charged is 84 basis points lower when voluntary accounting changes are excluded and 71 basis points lower when mandatory accounting changes are excluded. Our results suggest that borrowers are willing to pay substantially higher interest rates to retain accounting flexibility that may help them avoid covenant violations and to avoid duplicate record-keeping costs.